1991
DOI: 10.1063/1.347544
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity degradation in oxygen-aged polypyrrole

Abstract: The conductivity of doped polypyrrole, as high as 100 Scm−1 in freshly prepared samples, falls slowly with time on exposure to atmospheric oxygen. Typically, the fall in conductivity is fairly slow at room temperature, but the process can be accelerated by heating samples and measuring the decrease in conductivity as a function of time. Analysis of the kinetics of this process shows a preliminary, 120 min regime in which a surface adsorption-diffusion mechanism with an activation energy of 0.41 eV appears to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…It is well known that absorption of oxygen onto oxidized PPy leads to the decrease of conductivity, possibly by inhibiting the mobility of the charge carriers. 17,18 Furthermore, the second 1-week incubation apparently had a much greater impact than the first 1-week incubation in reducing the conductivity, meaning the increase of resistivity with incubation was nonlinear and accelerated in the second week. Because the second redoping was again able to greatly bring down the resistivity, it is believed that the increase of resistivity during the second week of incubation was also mainly caused by dedoping.…”
Section: Discussionmentioning
confidence: 96%
“…It is well known that absorption of oxygen onto oxidized PPy leads to the decrease of conductivity, possibly by inhibiting the mobility of the charge carriers. 17,18 Furthermore, the second 1-week incubation apparently had a much greater impact than the first 1-week incubation in reducing the conductivity, meaning the increase of resistivity with incubation was nonlinear and accelerated in the second week. Because the second redoping was again able to greatly bring down the resistivity, it is believed that the increase of resistivity during the second week of incubation was also mainly caused by dedoping.…”
Section: Discussionmentioning
confidence: 96%
“…Apart from this, the phenomena also points to the possibility of damage in conjugated PANI chain structure by atmospheric agents. The relationship between aerial oxidation and conductivity deterioration is studied by Tansley et al [33]. They reported that oxygen absorption occurs on the surface of polymers followed by its diffusion into the bulk.…”
Section: Thermal Stability Of DC Conductivitymentioning
confidence: 98%
“…9b) with S 1 showing more retention than S 2 . There are many changes occurring at high temperature causing deterioration of polymer structure and leading to decrease in conductivity of conducting polymers [25][26][27][28][29][30][31][32][33]. The thermal stability of conductivity of PANI depends upon the nature of dopant and on the morphology of the material.…”
Section: Thermal Stability Of DC Conductivitymentioning
confidence: 99%
“…OH and H 2 O 2 generated during the electrolysis on polymer matrix, resulting in the degradation of PPy film [41,42]. On the other hand, it is now known that conducting PPy tends to degrade and lose of part of its electronic conductivity on prolonged exposure to oxygen [43,44]. In addition, the longtime runs in aqueous solution also lead to the conformational relaxation of PPy film [45,46].…”
Section: The Stability Of the Aqds/ppy Composite Filmmentioning
confidence: 99%